A1.21 In-depth characterisation of CD24highCD38high transitional human B cells reveals different regulatory profiles. (13th February 2015) - Hillion, S; Simon, Q; Cornec, D; Mageed, R; Pers, JO
Abstract : CD24high CD38high transitional B cells represent a key stage in the developmental pathway of B cell peripheral tolerance and functional maturation. These B cells have been widely ascribed regulatory functions. However, the phenotypic and functional overlap between these cells and regulatory B cells remains controversial. In this study, we use multi-colour flow cytometry with bioinformatic analyses and functional studies to show that CD24high CD38high B cells can be differentiated into multiple subsets. The study also reveals for the first time that human transitional B cells encompass transitional type 1 (T1) and T2 B cells but also distinct anergic T3 B cells as well as IL-10-producing CD27 + transitional B cells. Interestingly, the latter two subsets differentially regulate CD4 + T cell proliferation and polarisation towards Th1 effector cells. Additional analyses show that the percentage of T3 B cells is reduced while the frequency of CD27 + transitional B cells is increased in patients with autoimmune diseases compared with matched healthy individuals. This study provides evidence for the existence of different transitional B cell subsets each displaying unique phenotypic and regulatory functional profiles. Furthermore, the study indicates that altered distribution of transitional B cells subsets highlights different regulatory defects in autoimmune diseases